Kesenjangan antara Prinsip Bagi Hasil dalam Ekonomi Islam dan Praktik Manajemen Risiko pada Koperasi Syariah: Tinjauan Literatur - Arnelia Putri Pratiwi; Dini Selasi (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
This research aims to analyze the gap between the profit-sharing principle as the normative foundation of Islamic economics and the risk management practices applied in sharia cooperatives, considering the ongoing inconsistencies in the implementation of the risk-sharing principle. The research method employs a qualitative approach thru literature study with thematic and comparative analysis techniques on relevant academic literature. The results and discussion indicate that sharia cooperatives tend to adopt a conventional risk management paradigm oriented toward institutional stability, thereby triggering the dominance of non-profit-sharing contracts and the shift of the concept of risk sharing to risk shifting in operational practices. The gap is influenced by structural factors, including limitations in managerial capacity, information asymmetry, potential moral hazard, and pressures of institutional sustainability. This study concludes that the risk management practices of sharia cooperatives do not fully reflect the principles of Islamic economics, thus necessitating a reconstruction of a more integrative and contextual risk management model. As a suggestion, sharia cooperatives need to develop a risk management framework based on risk sharing that is adaptive to operational risks without disregarding the values of justice and partnership as the main characteristics of Islamic economics.